2015
DOI: 10.1159/000380757
|View full text |Cite
|
Sign up to set email alerts
|

Atovaquone for Prophylaxis of Toxoplasmosis after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Toxoplasmosis and infections by other opportunistic agents such as Pneumocystis jirovecii constitute life-threatening risks for patients after allogeneic hematopoietic stem cell transplantation. Trimethoprim/sulfamethoxazole (TMP-SMX) has been well established for post-transplant toxoplasmosis and pneumocystis prophylaxis, but treatment may be limited due to toxicity. We explored atovaquone as an alternative and compared it with TMP-SMX regarding toxicity and efficacy during the first 100 days after transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In our series, 17.4% were breakthrough TXP, in accordance with 12% of breakthrough TXP reported by Gajurel et al [7]. Breakthrough TXP might reflect suboptimal dosing of prophylaxis related to inadequate oral absorption, mainly caused by gastrointestinal aGvHD, or drug interruptions because of haematotoxicity and gastrointestinal intolerance [7,19,20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our series, 17.4% were breakthrough TXP, in accordance with 12% of breakthrough TXP reported by Gajurel et al [7]. Breakthrough TXP might reflect suboptimal dosing of prophylaxis related to inadequate oral absorption, mainly caused by gastrointestinal aGvHD, or drug interruptions because of haematotoxicity and gastrointestinal intolerance [7,19,20].…”
Section: Discussionsupporting
confidence: 90%
“…High-dose trimethoprim-sulfamethoxazole (320/1600 mg/day) was shown to delay neutrophil recovery after HSCT [16] and a rather small (n ¼ 3) descriptive study reported that trimethoprim-sulfamethoxazole 160/800 mg/day impaired in vitro colony formation of peripheral blood stem cells [17]. However, retrospective studies (160/800 mg or 320/1600 mg thrice weekly) did not evidence significant delay in engraftment compared with no prophylaxis or atovaquone (1500 mg/day) [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis should ideally be started as soon as feasible after allo-HSCT but no later than engraftment and continued for at least six months, as about 10% of cases occur within one month and 90% of cases occur during within six months [ 26 ]. If engraftment is delayed and TMP/SMX cannot be given due to myelosuppression, atovaquone [ 27 ] can be used until engraftment, followed by TMP/SMX. A more controversial issue is the need for prophylaxis in ASCT recipients; such a policy is debatable due to the low incidence of toxoplasmosis in this setting and the consequent lack of experience.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of PJP prophylaxis, none of the 16 patients in the atovaquone arm (1500 mg 3 times a week) developed toxoplasmosis, but this study was conducted in low-risk autologous HCT recipients who generally do not even require Toxoplasma prophylaxis (9). A recent study showed no breakthrough toxoplasmosis in 22 patients after allo-HCT while on atovaquone prophylaxis (1500 mg daily) (10). Unfortunately, pre-HCT Toxoplasma serology of these patients is not mentioned, and thus it is not clear how many of these patients were at a high risk for reactivation.…”
Section: Failure Of Atovaquone Prophylaxis In Hematopoietic Cell Tranmentioning
confidence: 99%